Домінанти науково-дослідницьких зацікавлень Іларіона Слинька - Shatilova, Nataliia; Kulbabska, Olena (БДМУ, 2022)
The relevance of scientific research is determined by the importance of the scientist's scientific heritage as a separate milestone in the history of Ukrainian linguistic science. The purpose of the scientific work is to determine the main facets of the scientific and scientific-methodical activity of the outstanding Ukrainian grammarian and linguodidact, the founder of the syntactic school of the Chernivtsi University, Professor I. I. Slуnko. The research methodology is based on general scientific methods of analysis and synthesis, as well as specific linguistic methods ‒ descriptive with methods of classification and generalization of linguistic facts, logical comparison. Conclusions. Scientific achievements of Professor I. I. Slуnko (19.06.1912–01.01.1994) played an indisputable role in the development of linguistic studies not only in Bukovina, but also in Ukraine. In particular, two directions in the creative heritage of the scientist - the field of modern and historical syntax - are interconnected and complement each other, expressing the genesis of the formation of the syntactic system of the Ukrainian language on a national basis and the author's desire to preserve Ukrainian identity in the system of means of expressing thought. Promising are further studies of the linguistic personality of Ilarion Ilarionovуch Slуnko in all its manifestations ‒ temporal, spatial, evolutionary, cultural and aesthetic, status and social, linguoculturological, etc.
DOMINANT RESEARCH INTERESTS OF ILARION SLYNKO
Keywords: historiography, linguopersonology, I.I. Slynko, historical syntax, scientific and methodological activity, syntactic school of Chernivtsi University